2005
DOI: 10.1080/16506070510008461
|View full text |Cite
|
Sign up to set email alerts
|

A Burden to Others: A Common Source of Distress for the Terminally Ill

Abstract: Recent research into the desire for death among people with terminal illness has begun to recognize the importance of "feeling oneself a burden to others" as a factor in suicidal behaviour. In this study, 69 patients with advanced cancer underwent semi-structured interviews. The sense of self-perceived burden was found to be a common experience, reported by 39.1% of participants as a minimal or mild concern and by 38% as a moderate to extreme concern. The sense of burden showed a low correlation with physical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
123
2
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 158 publications
(138 citation statements)
references
References 28 publications
11
123
2
2
Order By: Relevance
“…Similarly, the findings of Rehnsfeldt et al (2014) study in Denmark, Sweden and Norway showed that patients care was carried out based on routinized care without considering individual's self-worth and dignity (Rehnsfeldt et al, 2014). Although there is lack of evidence regarding cancer patients' perception of dignity in Iranian context, but the findings of few studies suggest that the dignity of Iranian patients is not completely maintained in clinical settings (Wilson et al, 2005;Nayeri et al, 2011;Ebrahimi et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the findings of Rehnsfeldt et al (2014) study in Denmark, Sweden and Norway showed that patients care was carried out based on routinized care without considering individual's self-worth and dignity (Rehnsfeldt et al, 2014). Although there is lack of evidence regarding cancer patients' perception of dignity in Iranian context, but the findings of few studies suggest that the dignity of Iranian patients is not completely maintained in clinical settings (Wilson et al, 2005;Nayeri et al, 2011;Ebrahimi et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…In many circles, the term "death with dignity" is synonymous with the right to assisted suicide and euthanasia. 62,[67][68][69][70] Several studies have reported that loss of dignity is very closely linked to why patients have either sought or, in some instances, received deathhastening assistance. 62,69 -71 According to a US survey of physician-assisted suicide and euthanasia, loss of dignity was the reason cited by physicians in 53% of cases where prescriptions had been written for the purpose of hastening death (second only to discomfort other than pain in 79% of cases).…”
Section: Loss Of Sense Of Dignitymentioning
confidence: 99%
“…Wilson, et al 62 conducted one of the few studies to directly examine the notion of burden to others among a group of 69 patients with advanced cancer. A sense of burden to others was common in this group of patients: 39% reported a minimal to moderate concern and 38% reported moderate to severe levels of distress around being a burden to others, whereas only 23% reported that they experienced no sense of burden.…”
Section: Burden To Othersmentioning
confidence: 99%
“…This belief has been termed self-perceived burden, and it has been defined as "a multidimensional construct arising from care recipients' feelings of dependence and the resulting frustration and worry, which then lead to feelings of guilt at being responsible for the caregiver's hardship" (p. 111). 1 The prevalence of a problematic sense of self-perceived burden is quite high in some medical populations, ranging from 26% to 65% among patients receiving palliative care for cancer, [2][3][4][5][6] 65% to 70% among stroke survivors, 7,8 and over 70% among patients entering treatment for chronic nonmalignant pain. 9 Self-perceived burden has been correlated with measures of pain, disability, and depression in different patient groups.…”
Section: Introductionmentioning
confidence: 99%